GONADOTROPIN, ANTI MULLERIAN HORMON DAN ESTRADIOL PADA SINDROM OVARIUM POLIKISTIK - Maria Tri Setiani; Setyo Dwi Santoso; Rahajoe Imam Santosa (Jurnal SainHealth, 2021)
PCOS (Polycystic Ovary Syndrome) is an endocrine disorder characterized by anovulation and hyperandrogenism. It was found that about ±10% of women of reproductive age cause infertility so that it becomes a burden for partners physically, psychologically and materially. Increasing age affects a woman's fertility and menstrual cycle. The menstrual cycle in women is influenced by hormones, depression, weight, and lifestyle. Gonadotropin Releasing Hormone (GnRH) is released by the hypothalamus through a secretory process every 90 – 120 minutes which then binds to gonadotropin cells and stimulates Follicle Stimulating Hormone (FSH), Luteinizing Hormone (LH). FSH, LH levels will increase after puberty, FSH, LH, Anti Mullerian Hormone (AMH) and estradiol are very important in folliculogenesis. However, the interactions between the four hormones are not yet fully understood. The purpose of this review was to determine the correlation between LH/FSH Ratio, AMH and Estradiol in women with Polycystic Ovarian Syndrome (PCOS). This understanding is expected to increase knowledge about the pathophysiology of PCOS. This study uses secondary data from the Pramita Surabaya Clinic laboratory which is examined for reproductive hormones. Data from 228 women aged < 35 years with an average LH/FSH ratio (0.61), AMH (3.56 ng/dL), and estradiol (34.42 pg/mL) and 172 women aged 35 years with a mean ratio of LH/FSH (0.54), AMH (2.93 ng/dL), and estradiol (36.60 pg/mL). LH, FSH, AMH and Estradiol examinations were performed on the 2-4th day of menstruation. Bivariate correlation analysis was used to see the relationship between AMH and the LH/FSH ratio and AMH and estradiol. From the results, there was a positive correlation between the AMH value and the LH/FSH ratio and a positive correlation between AMH and Estradiol which showed that AMH had an effect on the secretion of LH, FSH and Estradiol. Keywords: infertility, LH/FSH, AMH, estradiol, SOPK